1999
DOI: 10.1093/intimm/11.9.1381
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of glycosylphosphatidylinositol-anchored proteins inhibits T cell growth but not function

Abstract: Accumulating evidence suggests that proteins tethered to the plasma membrane through glycosylphosphatidylinositol (GPI) anchors share common biological properties. In the present study we demonstrate that GPI-anchored proteins regulate T cell growth. Specifically, anti-TCR-induced proliferation was profoundly inhibited by co-immobilized mAb specific for Thy-1, CD48 and Ly6A/E. However, neither IL-2 production nor the effector function of cytotoxic T lymphocytes was impaired in these circumstances. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…Another line of thoughts is provided by studies dealing with the Ab-mediated recruitment of GPI-anchored proteins on T cells. Such studies have revealed profound similarities between all these molecules, and notably their capacity, following Ab-mediated mobilization, to inhibit clonal T cell expansion through the IL-2R pathway, while preserving the functions of the lymphocytes (48,49). An important issue will be to find out whether PrPC follows the signaling pathway common to most GPI-anchored proteins on T cells, a pathway that results in clonal size control, while leaving intact effector functions such as cytotoxicity or lymphokine production, or whether PrPC initiates its own specific signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another line of thoughts is provided by studies dealing with the Ab-mediated recruitment of GPI-anchored proteins on T cells. Such studies have revealed profound similarities between all these molecules, and notably their capacity, following Ab-mediated mobilization, to inhibit clonal T cell expansion through the IL-2R pathway, while preserving the functions of the lymphocytes (48,49). An important issue will be to find out whether PrPC follows the signaling pathway common to most GPI-anchored proteins on T cells, a pathway that results in clonal size control, while leaving intact effector functions such as cytotoxicity or lymphokine production, or whether PrPC initiates its own specific signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of GPI-anchored proteins by mAbs to CD48, CD55, CD59, and CD73, Thy-1, Ly-6, and sgp-60 readily affects T cell activity usually by the induction of T cell proliferation or IL-2 production (9,(43)(44)(45)(46). In contrast, under some experimental conditions mAb binding to GPI-anchored proteins led to inhibition (46 -48) or to a modulation of T cell activation (49). Moreover, T cells lacking GPI-anchored proteins, including GPI-deficient T cells derived from patients with paroxysmal nocturnal hemoglobinuria (50,51) and T cells derived from CD48…”
Section: Discussionmentioning
confidence: 99%
“…As a positive control for immunoblotting, immunoprecipitation of IL-2R␣, IL-2R␤, and IL-2R␥ was performed as described previously. 18 Immunoprecipitates or 150 Lfractions from sucrose gradients were resolved by sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE). Western blot analysis was performed using polyclonal rabbit anti-IL-2R␣, IL-2R␤, and IL-2R␥ (Santa Cruz Biotechnology, Santa Cruz, CA) followed by Protein-A-HRP.…”
Section: Immunoprecipitations and Immunoblottingmentioning
confidence: 99%
“…18 In addition, IL-2-induced signaling was inhibited in these circumstances. These results were consistent with a signaling defect in the responsiveness of T cells to endogenously produced IL-2.…”
Section: Immobilized Mabs Specific For Gpi-ap Inhibit Il-2-induced Prmentioning
confidence: 99%